2021
DOI: 10.2147/dddt.s328837
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of Network Pharmacology and Experimental Validation to Reveal the Mechanism of Chinese Medicine Formula Naotaifang in Treating Cerebral Ischemia-Reperfusion Injury

Abstract: Background: Cerebral ischemia-reperfusion injury (CIRI) is a crucial factor leading to a poor prognosis for ischemic stroke patients. As a novel Chinese medicine formula, Naotaifang (NTF) was proven to exhibit a neuroprotective effect against ischemic stroke, clinically, and to alleviate CIRI in animals. However, the mechanisms underlying the beneficial effect have not been fully elucidated. Methods: In this study, we combined a network pharmacology approach and an in vivo experiment to explore the specific ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…We performed a series of investigations to evaluate the pharmacology, efficacy, and safety of NTF for more than 20 years. Studies indicate that NTF and its extracts minimize the cerebral infarct size and improve neurological function by inhibiting inflammation, oxidative stress, and apoptosis (Liao et al, 2015;Lan et al, 2020;Yang et al, 2021;Zhao et al, 2021). Considering the shared pathogenesis pathways between HT-CSVD and ischemic stroke, and if HT-CSVD is not treated in time, it can gradually progress to stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed a series of investigations to evaluate the pharmacology, efficacy, and safety of NTF for more than 20 years. Studies indicate that NTF and its extracts minimize the cerebral infarct size and improve neurological function by inhibiting inflammation, oxidative stress, and apoptosis (Liao et al, 2015;Lan et al, 2020;Yang et al, 2021;Zhao et al, 2021). Considering the shared pathogenesis pathways between HT-CSVD and ischemic stroke, and if HT-CSVD is not treated in time, it can gradually progress to stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies indicate that NTF alleviates nerve damage and improves cognitive function by suppressing neuronal cell ferroptosis (Lan et al, 2020). This reduces the infarct volume and apoptotic neuronal cells as well as increases the density of dendritic spines and survival of neurons (Yang et al, 2021). One pharmacological study reports that the metabolic pathway regulated by NTF is mainly purine metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that Tongxinluo (TXL) also has anti-apoptotic cerebral ischemia protection by means of the Cx43/Calpain II/Bax/caspase-3 pathway, contributing to the prevention and therapy of I/R injury (Cheng et al, 2017). Additionally, Naotaifang (NTF) was detected to increase the expression level of Bcl-2 and decrease the expression level of Bax (Yang et al, 2021a). To further study the effect of Gualou Guizhi decoction (GLGZD) on MCAO I/R injury, the involved mechanism was mainly relevant to regulating PARP-1/AIF signal pathway (Nan et al, 2020).…”
Section: Active Ingredients Of Traditional Chinese Medicinementioning
confidence: 99%
“…Using the PubChem (https://pubchem.ncbi.nlm.nih.gov/) database [11], all validated compounds collected were converted into standard Canonical SMILES format, and the SMILES format files were imported into SWISS (http://www. swisstargetprediction.ch/) [12]and the Superpred website (http://prediction.charite.de/), and set the property "homo sapiens" to predict the targets of the compounds.…”
Section: Prediction Of Potential Targetsmentioning
confidence: 99%